Vibration analysis of a dual-rotor-bearing-double casing system with pedestal looseness and multi-stage turbine blade-casing rub. (September 2020) - Yang, Yang; Ouyang, Huajiang; Yang, Yiren; Cao, Dengqing; Wang, Kai
Highlights: A dual-rotor-bearing-double casing system with pedestal looseness and rub is set up. An experimental study is performed on a test rig for revealing dynamic responses at different rotational speeds. Effects of pedestal looseness and rub-impact on the vibration characteristics of the system are investigated. Abstract: Pedestal looseness and rotor-stator rub are two common faults in rotating machines. To increase the thrust-weight ratio and enhance fuel efficiency of aero engines, the structural design of a dual-rotor system has to address these two kinds of common faults. The aim of this paper is to gain insight into the vibration behaviours of a dual-rotor system with pedestal looseness and rotor-stator rub. Firstly, a dual-rotor-bearing-double casing system is modelled. After that, considering the effects of two disc imbalances, and pedestal looseness which exists in high pressure rotor, the rub-impact fault between the multi-stage turbine blades and the multi-layer casings is further introduced to the system. In combination with the distribution of soft and hard coatings, the impact stiffness of the rub-impact model is adjusted accordingly. Then an experimental study is performed on a dual-rotor test rig for verifying the validity of the theoretical model and revealing the dynamic responses at different rotor speed ratio. Finally, taking the stiffness of loosened pedestals, disc eccentricities, speed ratio, and initial gap as the key parameters, the potential effects of pedestal looseness and rub-impact on the dynamic characteristics of the dual-rotor system are investigated in detail.